The National Security Policy and its Relationship with the National Development Strategic Plan Peru by 2021 - Yovera Vilchez, José Guillermo (2019)
Currently the State doesn´t have a National Security and Defense doctrine approved with corresponding legal norm, this doesn´t allow to guide the planning of National Security and Defense in the different sectors: national government, regional government, local government, public and private organizations, causing each entity to look for different reference texts to define basic concepts related to National Security and Defense, many of which don´t conform to the Peruvian reality and result in confusion in their definitions. Therefore, this research focused on determining the deficiencies, regulatory disagreements, and theoretical discrepancies, which hinder the relationship between the National Security Policy and the National Development Strategic Plan Peru to 2021; with the purpose of identifying the causes that generate them, and build a base to propose the use of theories and new knowledge that improve their relationship. The study was carried out in the city of Lima at the facilities of SEDENA and EL CEPLAN. After concluding the investigation, it was determined that there are theoretical discrepancies in the design of the Policy, which hinders the relationship between the National Security Policy and the National Development Strategic Plan Peru to 2021; as a consequence of the lack of uniformity in the teaching of Policies.